The Impact of Social Media Use and Peer Pressure on Adolescent Cybercrime Behavior: The Mediation Role of Emotional Intelligence and Parental Supervision Moderation - Khostarina, Tina; Aisyah Rahmani Nasution, Nur; Ramida Safitri, Chayrina (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The use of social media has become an inseparable part of daily life, especially among teenagers. Social media also offers great potential in supporting learning. With access to various learning resources. To find out the influence of social media use and peer pressure on cybercrime mediated by emotional acuity and parental supervision. This study uses the Systematic Literature Review (SLR) approach to explore the relationship between social media use, peer pressure, cybercrime behavior in adolescents, emotional intelligence, and parental supervision. The results of this study are that excessive social media use and peer pressure can increase the risk of cybercrime behavior in adolescents, with low emotional intelligence as the main triggering factor. Emotional intelligence plays an important role as a mediator in reducing the negative impact of social media, while parental supervision can weaken the influence of peer pressure. The implications of these findings emphasize the need for collaboration between families, schools, and the government in developing educational programs that target emotional management and healthy social media use, to prevent the involvement of adolescents in illegal activities in cyberspace.Penggunaan media sosial sudah menjadi bagian yang tidak terpisahkan dalam kehidupan sehari-hari, khususnya di kalangan remaja. Media sosial juga menawarkan potensi besar dalam menunjang pembelajaran. Dengan akses ke berbagai sumber belajar. Untuk mengetahui pengaruh penggunaan media sosial dan tekanan teman sebaya terhadap kejahatan dunia maya yang dimediasi oleh ketajaman emosional dan pengawasan orang tua. Penelitian ini menggunakan pendekatan Systematic Literature Review (SLR) untuk mengeksplorasi hubungan antara penggunaan media sosial, tekanan teman sebaya, perilaku cybercrime pada remaja, kecerdasan emosional, dan pengawasan orang tua. Hasil penelitian ini adalah penggunaan media sosial yang berlebihan dan tekanan teman sebaya dapat meningkatkan risiko terjadinya perilaku cybercrime pada remaja, dengan rendahnya kecerdasan emosional sebagai faktor pemicu utamanya. Kecerdasan emosional berperan penting sebagai mediator dalam mengurangi dampak negatif media sosial, sedangkan pengawasan orang tua dapat melemahkan pengaruh tekanan teman sebaya. . Implikasi dari temuan ini menekankan perlunya kolaborasi antara keluarga, sekolah, dan pemerintah dalam mengembangkan program pendidikan yang menyasar pengelolaan emosi dan penggunaan media sosial yang sehat, untuk mencegah keterlibatan remaja dalam aktivitas ilegal di dunia maya.